2020
DOI: 10.1002/alz.12167
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk of dementia following hospitalization due to physical diseases: A multicohort study

Abstract: Introduction: Conventional risk factors targeted by prevention (e.g., low education, smoking, and obesity) are associated with a 1.2-to 2-fold increased risk of dementia. It is unclear whether having a physical disease is an equally important risk factor for dementia. Methods: In this exploratory multicohort study of 283,414 community-dwelling participants, we examined 22 common hospital-treated physical diseases as risk factors for dementia. Results: During a median follow-up of 19 years, a total of 3416 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 49 publications
2
27
1
Order By: Relevance
“… 8 Little is known regarding the association between types of cancers and incident dementia. It is also of great importance to confirm the associations of emerging risk factors for dementia including musculoskeletal disorders, painful conditions, 9 respiratory disorders (such as chronic obstructive pulmonary disease [COPD]), 10 , 11 chronic kidney disease (CKD), 12 and digestive disorders 13 with dementia in large prospective cohort studies. A recent prospective study has identified several physical diseases including erysipelas, hypothyroidism, duodenal ulcer, gastritis, and duodenitis (in addition to conventional risk factors), that may increase the long-term risk of dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Little is known regarding the association between types of cancers and incident dementia. It is also of great importance to confirm the associations of emerging risk factors for dementia including musculoskeletal disorders, painful conditions, 9 respiratory disorders (such as chronic obstructive pulmonary disease [COPD]), 10 , 11 chronic kidney disease (CKD), 12 and digestive disorders 13 with dementia in large prospective cohort studies. A recent prospective study has identified several physical diseases including erysipelas, hypothyroidism, duodenal ulcer, gastritis, and duodenitis (in addition to conventional risk factors), that may increase the long-term risk of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective study has identified several physical diseases including erysipelas, hypothyroidism, duodenal ulcer, gastritis, and duodenitis (in addition to conventional risk factors), that may increase the long-term risk of dementia. 13 However, this study is limited by investigating a small number of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We also report CIs adjusted for the corresponding confidence level (1 minus 0•0004). We estimated effect size independently from time to diagnosis and by time between health condition exposure and Alzheimer's disease diagnosis as follows: (0-2] years, (2-10] years, and (10)(11)(12)(13)(14)(15) years.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 This prodromal phase makes it more difficult to separate possible early symptoms from causal risk factors when describing the natural course of the disease. It also highlights the urgent need for observational prospective studies with long follow-up periods [8][9][10] to investigate the long-term relationship between medical conditions and dementia onset. 4 Epidemiological studies on the causes of Alzheimer's disease have focused on hypothesis-driven searches for potential risk factors in cohort studies on older people (mostly older than 60 years).…”
Section: Introductionmentioning
confidence: 99%
“…Although a data-driven approach is standard practice in rapidly progressing omics research, it is rarely used in epidemiological studies of dementia risk factors. 2,3 This innovative feature and large sample sizes are major strengths of the study. Compared with the traditional hypothesis-testing approach, data-driven epidemiological research is less subject to investigator biases, such as selective reporting of expected findings.…”
mentioning
confidence: 99%